Aprimoramento de estratégias de intervenção em vias não pavimentadas com base no novo SICRO - Noronha, Francisco Arthur Alves (2019)
Unpaved roads correspond to about 88% of the Brazilian road network. The inadequate use of Pavement Management in improving the procedures for maintenance of unpaved roads uncovers financial losses and poor quality of the rolling surface. In most cases, this is due to inadequate intervention processes, reflecting the costs associated with transport operations and user safety. Based on this issue, Santana (2006) proposed alternatives to enable the proper sizing of work teams, and inputs to be arranged in the most recurring maintenance services on unpaved roads, taking into account the costs involved in each intervention, allowing a satisfactory application. by the manager. The proposal in question was based on the System of Referential Costs of Works 2 (SICRO 2) of the National Department of Transport Infrastructure (DNIT), in force at the time. However, with the advent of the new SICRO, in the first half of 2017, the need to improve the model comes to light. Therefore, several studies were observed about unpaved roads, their recurrent defects, maintenance strategies and applications of Pavement Management on these roads. In addition, the innovations of the new SICRO were addressed, aiming to establish the cost composition method to be used in this work. Finally, after budgeting, the Unit Costs of the two proposals were compared, based on the monetary update of Santana's (2006) proposal, through the General Market Price Index (IGP-M). It was concluded that the implementation of the new SICRO caused changes in the cost composition of maintenance services on unpaved roads, treated in this work, making the final costs, in some cases, more expensive, in others, cheaper.